Jeeves & Wooster. The complete first season. [videorecording (DVD)] - Young, Robert, 1933-; Laurie, Hugh, 1959-; Fry, Stephen, 1957-; Bruce, Brenda; Wodehouse, P. G. (Pelham Grenville), 1881-1975 (A & E Television Networks : New Video Group [distributor], 2001)
This collection features the five premiere episodes of the series hailed as "irreistible" by critics and beloved by millions of fans worldwide. The inept clubman Bertie Wooster is rescued from various unpleasant situations by the suavely resourceful valet, Jeeves.